Inguinal Hernia And Hydrocele In Children - Wayan Mahayani, Ida Ayu; Darmajaya, Made (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 I n g u i a l h e r n i a a n d h y d r o c e l e i s a f a i r ly c o m m o n d i s ea s e i n c hi l d r e n . T h e s t u d y s h o w e d t h a t t h e i n c i d e n c e i n t h e U n i t e d S t a t e s r ea c h e d 10 - 20 o f 1000 l i ve b i r t h s , w i t h m o r e l o ca t i o n s h e r n i a o n t h e r i g h t s i d e a n d 10% bi l a t e r a l l y . H y d r o c e l e i s a c o ll ec t i o n o f f l u i d i n t h e p r o ce ss us v a g i n a li s , a n d i t c a n ca u s e s w e l l i ng i n t h e g r o i n o r s c r o t u m . I n g u i n a l h e r n i a s o cc ur w h e n a b d o mi n a l o r g a ns p r o t r ude i n t o t h e i n g u i n a l ca n a l o r s c r o t u m . In h e a l t hy b a b i e s, b a l l s s u rr o u n d e d by a c l o s e d r o o m , t h e t un i c a v a g i n a l i s o f t h e s c r ot u m . I n p o s t n a t a l l i f e , t h i s i s a po t e n t i a l s p ac e t h a t s h ou l d n ot b e r e l a t e d to t h e p e r i to n e u m . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Inguinal hernia, Hydrocele.